BOLTING OF RED BEET: PROBLEMS AND SOLUTIONS - V. I. Burenin; T. M. Piskunova; D. V. Sokolova (Овощи России)
Results of study of the collection accessions of red beet with different level of bolting resistance are presented. Nature of inheritance of this trait in progeny, and also its connection with other biological and economically valuable characters and properties is shown. Bolting resistant accessions and possibility of its use in breeding are described. The promising initial material is selected and recommended. The most rational solution of the bolting problems in the beet is the development of resistant varieties and hybrids. For this purpose, the early-spring and under-winter planting are used, as well as the seed germination at low (30C) temperatures. The availability of the various initial material studied by modern methods of researches plays a key role. When the collection accessions of beet were studied in the VIR Polar branch (The Murmansk Region), the following genotypes were identified: 1 – non bolting, 2 – weak bolting (less than 10% of bolting plants), 3 – moderately bolting (10-50%), and 4 – high bolting (more than 50% of bolting plants). As a result of screening of a gene pool, the genetic sources of bolting resistance of beet were identified. At its crossing with bolting accessions the dominance of the trait «bolting» and monogenic nature of its inheritance are confirmed. For the purpose of beet breeding for bolting resistance, the symphycarpous varieties characterized by complex biological and agronomic characters (increased yield, cold tolerance, quality of production and resistance to blackleg) are the most usable. The cultivars Banko from Sweden (donor), Podzimnyaya A-0474 (VNIISSOK) and Polyarnaya ploskaya-249 (Polar branch VIR) are recommended as a genetic sources of bolting resistance.